Analisis Laporan Keuangan PT Waskita Karya (Persero) Tbk Terhadap Kinerja Keuangan Tahun 2021 - Anzelina, Rahma Septi (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
This study aims to determine and analyze the financial performance of PT Wijaya Karya Tbk as seen from the financial ratios. In this study, the financial performance of PT Wijaya Karya Tbk using financial ratios in the form of liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The research method used is descriptive quantitative. The data used are secondary data from the financial statements of PT Wijaya Karya Tbk for the period 2020 and 2021. The results of research on the profitability ratio of the company PT Waskita Karya (Persero) Tbk are experiencing bad conditions. The company's financial performance solvency ratio level is in quite good condition. This indicates that the company is still unable to utilize the assets it owns and the high cost of goods sold is borne so that the company produces less than optimally and experiences losses. Keywords: Fiancial Statement, Financial Performance, Financial Ratio